2020
DOI: 10.1002/erv.2724
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of the early maladaptive schemas in social situations in anorexia nervosa

Abstract: Background: Patients with anorexia nervosa (AN) show an impairment in the recognition and expression of emotions, as well as an increased sensitivity to being socially excluded, and rigid maladaptive schemas. The Cyberball paradigm is a virtual ball-toss game that can simulate social exclusion and inclusion. Our aim is to evaluate how cognitive schemas can influence the perception and the evaluation of the experiences of social inclusion/exclusion.Methods: Thirty-two AN patients and 34 healthy controls comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 82 publications
3
29
0
1
Order By: Relevance
“…social isolation, and defectiveness could be dysfunctional coping strategies that characterized ED patients and that might be taken under consideration, especially in people with traumatic history (Sarin and Abela, 2003;Dakanalis et al, 2014;Pauwels et al, 2018;Meneguzzo et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…social isolation, and defectiveness could be dysfunctional coping strategies that characterized ED patients and that might be taken under consideration, especially in people with traumatic history (Sarin and Abela, 2003;Dakanalis et al, 2014;Pauwels et al, 2018;Meneguzzo et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients with traumatic histories have exhibited higher levels of personality traits and EMS than patients without a history of trauma (Unoka et al, 2010;Trottier and MacDonald, 2017;Scharff et al, 2021). Previous findings have shown that both personality traits and EMS have a role in the development of clinical profiles that are closely correlated with the emotional factors targeted in EDs treatment (Moulton et al, 2015;Trottier and MacDonald, 2017;Aloi et al, 2020;Meneguzzo et al, 2020a). Personality traits linked to multi-impulsivity behaviors like borderline, antisocial, and paranoid personality have been linked to the cascade effects of traumatic events in ED patients, with dysfunctional coping behaviors adopted in order to avoid thoughts, emotions, and memories (Sansone and Sansone, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these unpleasant emotions will affect patients' social adjustment and therefore deteriorate their social relations. If an individual is afraid and insecure or perceives any situation as a threat or danger, it is difficult for them to relate to others, and consequently, these feelings can lead to social isolation, which is a key maintaining factor of the disorder (Kan and Treasure, 2019;Meneguzzo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Physical Appearance Comparison Scale (PACS) [46] was used to measure the subjects' tendency to compare their physical appearances with others in various social situations. The Italian version was already validated in a previous study [47]. The PACS is a 5-item Likert scale with five possible answers, ranging from "never" to "always."…”
Section: Physical Comparisons At Social Eventsmentioning
confidence: 99%